The effect of female directions on capital structure - Md Shahrul Shafiq, Mohd ali Basha (2018)
This study examines the relationships between female directors proxies by number of women sits on board, female directors expertise and independent female directors and capital structure of the 100 largest public listed companies in Malaysia based on market capitalization excluding the financial institutions. In addition, the study utilizes 2016 annual report. Results show approximately 16 percent of female sits on Malaysia board of directors. This study shows that there is still far from expected to achieve 30 percent in year 2017 as announcement of the Malaysian Code on Corporate Governance in 2017. This study has founds positive significant relationships between firm size, tangibility and capital structure. The negative relationships on liquidity are significant, which have strongly influence the firm’s capital structure. Then, positive insignificant have been shown by the number of women sits on board, independent female directors, board size, and board composition. Furthermore, female directors expertise, firm age, and investment opportunities have negative insignificant relationship with the firm’s capital structure. The study also provides suggestions and recommendations for future research work.